Value of the visual prostate symptom score in evaluation of symptomatic benign prostatic enlargement: prospective study in a Nigerian population - Onowa, Victor E.; Shuaibu, Samaila I.; Akpayak, Idorenyin C.; Ofoha, Chimaobi G.; Agbo, Christian A.; Nabasu, Lemech E.; Galam, Zingkur Z.; Ramyil, Venyir M.; Dakum, Nuhu K. (International Journal of Research in Medical Sciences, 2019)
Background: To evaluate the correlation of Visual Prostate Symptom Score (VPSS) with International Prostate Symptom Score (IPSS) and Maximum Urinary Flow (Qmax). To investigate the effect of educational level on the ability to independently complete the VPSS versus the IPSS and time taken to do so. Methods: Bio data was taken from men with lower urinary tract symptoms (LUTS) due to Benign Prostatic Enlargement (BPE) who presented at the Urology clinic of Jos University Teaching Hospital. They were administered the IPSS questionnaire and VPSS pictogram, which they completed with or without physician assistance and the time taken to do so was noted. They subsequently had uroflowmetry done on same visit and the data was recorded in a structured proforma. Statistical analysis was done using SPSS(R) version 20. Correlation test was done for VPSS, IPSS and Qmax while the paired t-test was used for the average time spent in completing both questionnaires. A p-value <0.05 was considered as significant. Results: Eighty-five men (aged 42 to 94 years) were enrolled in the study. The VPSS correlated significantly with the IPSS in terms of total score (r = +0.684, p<0.001) and QoL (r = +0.570, p<0.001), as well as with the Qmax (r = -0.222, p = 0.041). A greater proportion (21.2%) of men with limited education could complete the VPSS without physician assistance as compared to the IPSS (6.0%) and the average time taken to complete the VPSS (170.51 seconds) was significantly shorter than the time taken to complete the IPSS (406.42 seconds). Conclusions: The VPSS correlates significantly with the IPSS and Qmax. It can be completed without physician assistance by a greater proportion of men with limited education within a shorter time period.